General non‐isospectral integrable coupling of AKNS equations associated with so(3, R). (3rd May 2018) - Yu, Jing; Yuan, Wenbo; Han, Jingwei
Abstract : By means of the real Lie algebra s o ( 3, R ) and compatible condition of spectral problems, a general non‐isospectral AKNS equations is constructed. Furthermore, by enlarging spectral problems, the corresponding non‐isospectral integrable coupling of AKNS equations associated with s o ( 3, R ) is also obtained in this paper.